US multinational enterprises: Effects on poverty in developing countries - Omar Neme Castillo; Cesaire Chiatchoua (Research in Globalization, 2022)
The aim of the paper is to determine the effect of the Multinational Enterprises of the United States (US-MNE) in the reduction of poverty in a group of 18 developing countries where they operate for the period 2009-2018. Furthermore, the determining factors of the attraction of US-MNE to these countries are estimated and it is tested whether they affect poverty. A dynamic panel data econometric methodology (sys-GMM) is followed. It is found that US-MNE positively influence poverty reduction, and that significant determinants for attracting these companies are at the same time poverty reducing factors. Consequently, the US-MNE can be considered as a central mechanism of the dynamics of poverty in developing countries. The document contributes to the limited literature that quantitatively analyses the role of MNE in reducing poverty.
Keywords: 330; Developing countries; Multinational enterprises; Poverty; United States